Perilaku Ramah Lingkungan dan Tidak Ramah Lingkungan dalam Perladangan Berpindah pada Masyarakat Tolaki di Routa Kabupaten Konawe - Sarlan Adijaya (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This article is intended to reveal environmentally friendly and environmentally unfriendly practices in shifting cultivation among the Tolaki people in Southeast Sulawesi. The method of presenting this article is done by first describing the practice of shifting cultivation as it is and then showing environmentally friendly and non-environmentally friendly practices at each stage. The results of this study indicate that there are environmentally friendly and unfriendly behaviors in shifting cultivation practices. Environmentally friendly behaviors include: a ceremony to apply for a permit to clear a field (mohoto o wuta), allowing a number of trees to stand upright in some parts of the field, cleaning the entire side of the cultivated area when they want to burn (mekere), getting to know the fallow and rotary mechanism as well as the practice of hetero-culture inside it. Meanwhile, environmentally unfriendly practices include: the habit of burning on wood stumps that can still grow, slashing and cleaning up new shoots of wood and piling grass and other debris on the stumps.